2018
DOI: 10.1007/s00264-018-3836-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the anterior boundary of necrotic lesion on the occurrence of collapse in osteonecrosis of the femoral head

Abstract: This study indicates that ONFH patients with anterior localization of a necrotic lesion can develop collapse even if the necrotic lesion is medially located.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 23 publications
1
55
0
Order By: Relevance
“…Karasuyama suggested that stress concentration along the lateral sclerotic boundary triggered the subchondral fracture and finally induced the femoral head collapse. Kubo reported different collapse rates of 0%, 23%, and 81%, respectively, corresponding to different locations of lateral sclerotic boundary at the medial one‐third, the middle third, and the lateral one‐third of the weight‐bearing portion of the acetabulum, and he found that the anterior sclerotic boundary could also have an impact on the risk of collapse. Utsunomya generated patient‐specific FEM from 51 patients with ONFH, and he reported that stress was equally distributed on the femoral head surface in all FEM of ARCO Stage I hips, but stress was concentrated at the lateral boundary of the femoral head surface in all FEM of both ARCO Stages II and III hips, which is in accordance with the low‐intensity band on T1‐weighted MRI images, sclerotic changes on CT images and subchondral fractures on micro‐CT images.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Karasuyama suggested that stress concentration along the lateral sclerotic boundary triggered the subchondral fracture and finally induced the femoral head collapse. Kubo reported different collapse rates of 0%, 23%, and 81%, respectively, corresponding to different locations of lateral sclerotic boundary at the medial one‐third, the middle third, and the lateral one‐third of the weight‐bearing portion of the acetabulum, and he found that the anterior sclerotic boundary could also have an impact on the risk of collapse. Utsunomya generated patient‐specific FEM from 51 patients with ONFH, and he reported that stress was equally distributed on the femoral head surface in all FEM of ARCO Stage I hips, but stress was concentrated at the lateral boundary of the femoral head surface in all FEM of both ARCO Stages II and III hips, which is in accordance with the low‐intensity band on T1‐weighted MRI images, sclerotic changes on CT images and subchondral fractures on micro‐CT images.…”
Section: Discussionmentioning
confidence: 99%
“…reported that only 59% of hips became collapsed during a follow‐up period of 5–15 years when left untreated. Kubo reported a collapse rate of 54.0% among 113 asymptomatic hips during a follow‐up period of 2.0–11.8 years. Zhao reported that only 42.73% of hips progressed to femoral head collapse during 7‐year follow‐up.…”
Section: Introductionmentioning
confidence: 99%
“…Occurrence of collapse remains difficult to predict. Radiologic [17][18][19][20] and biologic [21] markers, site of necrosis, volume of osteonecrosis, and etiology of osteonecrosis are discussed in this issue.…”
Section: Risk Of Collapse and Quality Of Lifementioning
confidence: 99%
“…The degree of collapse was also measured according to evaluated by concentric circles on both anteroposterior and lateral radiographs using ImageJ (1.52a, National Institutes of Health, USA), referring to previous literatures [16,17]. With the increasing progression of femoral head collapse, lateral subluxation was defined when Shenton's line was not continuous.…”
Section: Methodsmentioning
confidence: 99%